Conceptual Analysis of It Media Integration In The Digital Islamic Education Curriculum As An Effort To Strengthen The Character Of Junior High School Students: A Library Perspective - Syaifuddin, Syaifuddin; Junaedi, Junaedi (Annpublisher, 2025)
Background. Digital transformation in the world of education demands a shift in the learning paradigm of Islamic Religious Education (PAI), particularly in strengthening the character of junior high school students. Aims. This research aims to formulate a conceptual model for the integration of information technology (IT) media into the digital PAI curriculum as an instrument for the formation of Islamic character. Methods. Using a qualitative approach through library research and descriptive-analytical methods, this study analyzes academic literature from the past decade using content analysis and thematic analysis techniques. Result. The study results in the ISLAMIC-TECH model, which includes five main components: Infrastructure, Spiritual Content, Learning Activity, Assessment, and Moral Character, as an integrative foundation between technological, pedagogical, and spiritual dimensions. Four effective IT media typologies in PAI learning have been identified, namely: immersive media (VR/AR), interactive (gamification), collaborative (social learning), and adaptive (personalized learning). The implementation strategy emphasizes the principle of